Analisis Problemtika Negara-Negara Berkembang Mayoritas Muslim dalam Pembangunan Ekonomi - Anwar, Sepiana; Zabrina, Tacika Nur; Haliza, Siti Nur; Ramadhan, Irsyadi; Yetti, Fitri (Islamic Economics and Business Review, 2024)
Abstract This research examines these to understand the clash. This is not necessarily in accordance with the needs and characteristics of the people in these countries. In addition, the role of education in providing access and skills to society is analyzed to understand its relationship with economic development, but also focuses on aspects of economic and social inequality, and the impact of inequality is then discussed in this research. Concerning equal distribution of economic opportunities and community participation in economic development. To understand how political factors influence the investment environment and economic growth, we evaluate political stability as a determinant of sustainable economic development. Through a detailed analysis of these issues, this study can provide a deeper understanding of the serious challenges facing developing countries with a majority Muslim population and provide a basis for establishing more effective and comprehensive policies to support sustainable economic development. Keywords: Developing country; Muslim majority; Economic Policy Abstrak Penelitian ini mengkaji hal ini untuk memahami benturan. Hal ini belum tentu sesuai dengan kebutuhan dan karakteristik masyarakat di negara-negara tersebut. Selain itu, peran pendidikan dalam memberikan akses dan keterampilan kepada masyarakat dianalisis untuk memahami hubungannya dengan pembangunan ekonomi, namun juga berfokus pada aspek kesenjangan ekonomi dan sosial, dan dampak kesenjangan kemudian dibahas dalam penelitian ini. Tentang pemerataan peluang ekonomi dan partisipasi masyarakat dalam pembangunan ekonomi. Untuk memahami bagaimana faktor politik mempengaruhi lingkungan investasi dan pertumbuhan ekonomi, kami mengevaluasi stabilitas politik sebagai faktor penentu pembangunan ekonomi berkelanjutan. Melalui analisis rinci terhadap isu-isu tersebut, studi ini dapat memberikan pemahaman yang lebih mendalam mengenai tantangan serius yang dihadapi negara-negara berkembang yang mayoritas penduduknya Muslim dan memberikan dasar untuk menetapkan kebijakan yang lebih efektif dan komprehensif untuk mendukung pembangunan ekonomi berkelanjutan. Kata kunci: Negara Berkembang; Mayoritas Muslim; Kebijakan Ekonomi